Motivasi Kerja pada Driver Go-Car Ditinjau dari Psychological Contract dan Person-Organization Fit - Ika Puspitasari; Aditya Nanda Priyatama; Selly Astriana (Jurnal Manajemen dan Kewirausahaan, 2018)
Human resources is an important factor in the organization. This reason  underlied the need to create work motivation in working field. Motivation is influenced by the desire to achieve goals, both individual goals or organization goals. Those can be seen through psychological contract and person-organization fit. The purpose of this study is: 1) to determine the relation of psycological contract and person-organization fit with work motivation on the go-car drivers, 2) to determine the relation between psycological contract with work motivation on the go-car drivers, 3) to determine the relation between person-organization fit with work motivation on the go-car drivers. This study uses a purposive random sampling with sample of 81 go-car drivers in Surakarta.     The result of this research shows there is a significant positive relation between psychological    contract and  person-organization fit with work motivation on the go-car drivers  https://doi.org/10.26905/jmdk.v6i2.2357